EFFECT OF GRAIN MOISTURE OF CORN AT HARVESTING ON SOME AGRONOMIC TRAITS - & Alkazaali, Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted during spring and fall seasons, 2015 , at the fields of Field Crop Department – College of Agriculture –University of Baghdad . The objective was to study the effect of grain moisture at  harvesting on some agronomic traits  of the corn  next  generation , by  using synthetic variety 5018 . In spring season 2015 , seeds of this variety  was planted ,when  moisture of the ear grains was (37-42%) , ten ears were harvested. Ear harvesting dates were performed manually when the grains had 37-42% , 34-36% , 30-33% , 25- 28% and 19-22%  moisture content. In fall season  2015 , varietal trail was carried out to the five treatment materials , using Randomized Complete Bock Design , with four replicates. The results  revealed , that non significant differences between treatments (19-22)%  and  (25-28)% , in all the studied traits . The plants  grown from the seeds of (25-28)%, were produced  highest vegetative mass (116.30 g.plant-1) , total dray matter (269 g. plant-1) and total dray matter ( 1.80  kg.m-2 ) . Highest grain yield ( 1.07  kg.m-2 ) and harvesting index ( 0.63) were produced from plants grown from  seeds harvested  with (19-22)%  moisture content . It can be concluded  that the best moisture contents of the grains for seed production was (19-28)%.